Pengembangan sistem informasi nilai rapor (sinara) Kurikulum 2013 berbasis web - Supriyatno Supriyatno; Supriyoko Supriyoko (Universitas Sarjanawiyata Tamansiswa, 2015)
This study aims : [1] to develop an information system as one of the alternative data management of student report to be more effective. [2] resulted in an application of Information System of Curriculum 2013 student report using web-based [3] to determine the feasibility of the product Information System of 2013 Curriculum student report using web-based. The study subjects are an assessor of Information Technology and Communication who evaluated the design and the initial product, fourteen teachers did the test of the first operational products and fifty-four teachers evaluated the second operational products. The research data are qualitative and quantitative. The qualitative data captured was to determine the correctness of the design, the correctness of system and security of systems, that used in the checklist evaluation form and narrative questions, while quantitative data captured was to examine the feasibility of the products covering aspects of the web display, based on presentation and the effectiveness and the efficiency using the questionnaires. The results of this study show that: [1] Information System of curriculum 2013 student report is good, from the aspects of the display, the presentation and it has high effectiveness and efficiency as the data management of students report [2] Information System of curriculum 2013 students report using web-based has also high productivity. In general Information System of 2013 Curriculum is feasible as the data management of curriculum 2013